Analisis Keberhasilan Petisi Online Dalam Merubah Keputusan - Syeham Surya Abadi; Sayyed Tangguh; Wisnu Saputra; Yangggi Suhawa (UIN Sunan Gunung Djati Bandung, 2023)
Public wishes can be dealt with mostly through public policy. However, governments are often unable to solve all the problems of society as a whole. This is because the interests, needs, and perspectives of each person on the current situation are different. To address this, making an online petition is now easier, beneficial, and effective, and can be done anywhere. Change.Org is an online platform that helps people make online petitions and collect petitions from the community to promote social change related to political or social issues. The platform also helps petition creators get public signatures. The method used is descriptive with a qualitative approach. Researchers use a qualitative approach because focusing on processes rather than outcomes, researchers want to gain an idea of meaning, understanding through word descriptions, and build abstractions, concepts, hypotheses and theories through the details of the discoveries the researchers find. This method further describes the aspects, the context of each word, the images uploaded in the online petition on the Change.Org platform. Based on the results of the research, it can be concluded that only five petitions meet five indicators of online petition success. However, online petitions are not the only component that influences the decision-making process; the execution process beyond online petition also plays an important role in such decision making